Improving Geographical Skills Through Geospatial Technology Based Tools Among High School Students - Nuri Hidayati; Helfia Edial (Postgraduate, University of Mataram, 2026)
This study aims to analyze improvements in students’ geographic skills, determine the effect of using geospatial technology-based tools on geographic skills, and describe “learning to learn” skills in geography instruction. The study employed a quantitative approach with a quasi-experimental nonequivalent control group design. The study sample consisted of 48 10th-grade students at SMAN 3 Siak, comprising 25 students in the experimental class and 23 students in the control class. Data were collected through pretest–posttest tests, observations, and documentation, then analyzed using descriptive statistics, the N-Gain test, normality tests, homogeneity tests, and simple linear regression with the aid of IBM SPSS 26. The results showed that the average score of the experimental class increased from 59.72 to 77.00, while that of the control class increased from 48.52 to 67.22. The N-Gain value for the experimental class (0.41) was higher than that of the control class (0.38). Regression analysis showed that the use of geographical tools had a positive and significant effect on geographical skills (F = 27.667; p < 0.001) with a coefficient of determination (R²) of 0.376. This approach also helped develop students’ “learning to learn” skills. Thus, geospatial technology-based tools are effective in improving geographic skills and supporting contextual, independent, and 21st-century competency-oriented geography learning.